Immigration, integration and terrorism: is there a clash of cultures? - Justina Fischer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We test whether immigrants are more prone to support terror than natives because of lower opportunity costs, using the international World Values Survey data. We show that, in general, economically, politically and socially non-integrated persons are more likely to accept using violence for achieving political goals, consistent with the economic model of crime. We also find evidence for the destructive effects of a `clash of cultures': Immigrants in OECD countries who originate from more culturally distanced countries in Africa and Asia appear more likely to view using violence for political goals as justified. Most importantly, we find no evidence that the clash-of-cultures-effect is driven by Islam religion, which appears irrelevant to terror support. As robustness test we relate individual attitude to real-life behavior: using country panels of transnational terrorist attacks in OECD countries, we show that the population attitudes towards violence and terror determine the occurrence of terror incidents, as does the share of immigrants in the population. A further analysis shows a positive association of immigrants from Africa and Asia with transnational terror, while the majority religion Islam of the sending country does not appear to play a role. Again, we find that culture defined by geographic proximity dominates culture defined by religion.
Keywords: K42; H56; O15; 330; terror; terrorism; violence; conflict; immigration; culture; integration; crime